Cochlear implantation in chronic otitis media with and without cholesteatoma: Surgical considerations and auditory outcomes - Gülhan Yaşar, Nagihan; Karamert, Recep; Tutar, Hakan; Uğur, Mehmet Birol; Hazır, Burak; Bayazıt, Yıldırım Ahmet (Karger, 2021)
Introduction: Cochlear implant (CI) surgery is a safe and standardized procedure in the presence of normal temporal bone anatomy. However, in the surgery of patients with chronic otitis media (COM), the surgeon may encounter several problems. The aim of this study was to evaluate the impact of COM with and without cholesteatoma on surgical and auditory outcomes of CIs. Methods: The study group consisted of 39 patients with COM who received CIs. Age- and gender-matched 38 standard CI patients served as controls. The surgical techniques and complications, pure tone audiometry (PTA) scores, speech discrimination scores (SDS), and the International Outcome Inventory for Hearing Aids (IOI-HA) questionnaire results of the groups were compared. Results: The presence of COM was associated with a higher rate of complication than controls. Staging the surgeries, presence or absence of cholesteatoma, and type of surgical technique were not associated with surgical outcomes and complications (p > 0.05). There was no significant difference between the groups in terms of postoperative PTA scores, SDS, and IOI-HA scores (p > 0.05). Conclusion: Postoperative complications like device failure and skin breakdown are increased in cases of COM compared to standard CI surgeries. However, that increase is not associated with staging the surgeries, presence or absence of cholesteatoma, and type of ear surgery performed. It is advocated to close the external ear canal and eustachian tube without mastoid obliteration in the presence of a radical mastoidectomy cavity, which will decrease the postoperative complication rates and allow for radiological follow-up with computed tomography for the possibility of cholesteatoma recurrence. The auditory benefits of CI in patients with and without COM are comparable.
Keywords: Cochlear Implant; Chronic Otitis Media; Cholesteatoma